Investigating the Effects of Store-Brand Introduction on Retailer Demand and Pricing Behavior - Chintagunta, Pradeep K. (Institutional Knowledge at Singapore Management University, 2002)
The effects of the introduction of a store-brand into a particular product category are studied. The paper focuses on the effect of store-brand introduction on the demand as well as on the supply side. On the demand side, the changes in preferences for the national brands and price elasticities in the category are investigated. On the supply side, the effects of the new entrant on the interactions between the national brand manufacturers and the retailer introducing the store brand are studied, including how these interactions influence the retailer's pricing behavior. In doing so, it is possible to test whether the observed data are consistent with some of the commonly used assumptions regarding retailer pricing behavior. In examining the nature of manufacturer interactions with the retailer, the manufacturer of the national brand appears to take a softer stance in its interactions with the retailer subsequent to store-brand entry. This finding is consistent with academic research and with articles in the popular press which suggest that the store brand enhances the retailer's bargaining ability vis-a-vis the manufacturers of the national brands.